Does post-disturbance salvage logging affect the provision of ecosystem services? A systematic review protocol. Issue 1 (December 2015) - Leverkus, Alexandro; Gustafsson, Lena; Rey Benayas, José; Castro, Jorge
Abstract Background Forest fires, insect outbreaks, and windstorms are common forest disturbances that are expected to increase in importance in coming decades. Post-disturbance management often involves salvage logging, i.e. the felling and removal of the affected trees. However, harvesting these biological legacies may represent a second disturbance whose effects on ecosystem processes add on those of the initial disturbance. Many of the potentially affected processes, such as soil erosion and stream water quality, represent regulating and supporting ecosystem services important for human society. In the last 15 years, much empirical evidence has been gathered on the ecological consequences of this management practice, and it has now become necessary to synthesise this evidence in meaningful ways for managers and decision-makers. Methods With this systematic review we aim to synthesise the literature on the effects of salvage logging on ecosystem services and determine the effects of major effect modifiers such as disturbance type and intensity, the timing and method of logging, and the type of forest. We will conduct searches of the primary scientific literature, which will be selected and categorised according to its relevance to the topic and its quality. Each relevant article will be read in full to obtain the necessary data for meta-analysis and to identify its main conclusions. Mixed-effects models will be performed to assess the effects of the identified effect modifiers on the effect sizes of the salvage intervention on ecosystem services and to account for random effects arising from studies being performed in the same area. Sensitivity analyses will test the potential effects of study quality, and publication bias will be assessed with the trim and fill method. We will present the results as a narrative review and a meta-analysis.